Parathyroid Gland Disorders Controversies and Debates - Sakr, Mahmoud F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book offers a comprehensive overview of all parathyroid gland disorders both, benign and malignant. It emphases established concepts, presents the ongoing controversies, challenges and debates on diagnosis and treatment of different parathyroid gland disorders, with a view of clarifying some uncertainties, making suggestions to resolve others, and establishing strategies to reach therapeutic success.In addition to general information on parathyroid gland embryology, surgical anatomy, histology and physiology, the chapters explore hyperparathyroidism, osteitis fibrosa cystica, hypoparathyroidism, hungry bone syndrome, the importance of calcium in the human body and differential diagnosis of hypercalcemia. The last chapters investigate post-thyroidectomy hypocalcemia, thyroid cancer, recent intra-operative localizing tools, and illustrate new techniques of parathyroidectomy, as well as parathyroid transplantation. The book will be an invaluable and indispensable source of knowledge and reference for all specialists and trainees entrusted with the care of patients suffering from parathyroid disease.
Parathyroid Glands: Historical Review -- Embryology of the Parathyroid Gland -- Surgical Anatomy of the Parathyroid Gland -- Histology of the Parathyroid Gland -- Physiology of the Parathyroid Gland -- Calcium: Why is it Important? Hyperparathyroidism (HPT) -- Osteitis Fibrosa Cystica -- Hypoparathyroidism -- Metabolic Syndromes of Parathyroid Failure -- Hungry Bone Syndrome -- Post-thyroidectomy Hypocalcemia: Incidence and Risk Factors -- Post-thyroidectomy Hypocalcemia: Clinical Presentation -- Post-thyroidectomy Hypocalcemia: Prevention -- Parathyroid Transplantation -- Parathyroid Cancer -- Intra-operative tools in Parathyroidectomy -- Parathyroidectomy.
Keywords: Otorhinolaryngology; Endocrinology; Oncology; Mouth -- Surgery; Otorhinolaryngology; Endocrinology; Oncology; Oral and Maxillofacial Surgery; Parathyroid Glands; Parathyroid Diseases